Analysis of Sustainable Food Sector Development in the Sumatra Island - Suirlan, Rita; Nurnaningsih, Nurnaningsih (Faculty of Economics, Universitas Sriwijaya, 2024)
The research aims to analyze the development of food security through indicators of the sustainable food sector on the island of Sumatra in 2018-2022. Food sector indicators include the number of poor people, food inflation, rice consumption per capita, insufficient food consumption, and food insecurity. Food security indicators use the food security index. The research method is quantitative through secondary data collection with panel data analysis from cross section results of 10 provinces on the island of Sumatra and time series data for 2018-2022. The approach used, namely CEM,FEM, REM. The research findings show that the food inflation variable has a positive and significant effect on the food security index, the poor population variable, rice consumption per capita, insufficient food consumption has a positive and insignificant effect on the food security index. Population with food insecurity has a negative and insignificant effect on the food security index.